Role of Work Environment and Organizational Culture to Job Performance - Putra, Arif Rahman; Hariani, Mila; Nurmalasari, Dita; Irfan, Mochamad; Hakim, Yusuf Rahman Al (Journal of Islamic Economics Perspectives, 2020)
ABSTRACT Improving the quality of human resources is focused on a variety of things that can affect job performance. There are two variables that are thought to have contributed to the formation of job performance, namely the work environment and organizational culture. This study aims to analyze and determine the effect of the work environment and organizational culture on job performance. The research will be conducted in one of the micro businesses in Kranggan District, Mojokerto Regency which involves 25 employees to be involved as respondents. Multiple linear regression analysis is used as an analytical tool to prove the research hypothesis. The research findings suggest that (1) the work environment has a significant effect on job performance; (2) organizational culture has a significant effect on job performance; and (3) work environment and organizational culture simultaneously have a significant effect on job performance. Keywords: work environment, organizational culture, job performance